The Sale of Genetic Material in Islamic Jurisprudence and Law A Comparative Study - Hussein, Prof.Dr. Zubair Mustafa Hussein; Omar, Asst.L. Avista Salar Omar (Sulaimani Journal for Humanities, 2025)
As a result of scientific development, it has become possible to utilize genetic material either by adding specific traits to a gene or for the purpose of treating a particular disease, aiming to maintain social stability. This, in turn, led to contracts involving genetic material, facilitated by the availability of financial resources and the accessibility for patients, as well as the urgent need of healthy individuals for money or their hope of improving their financial situation, which sometimes prompted the poor to sell their genetic material. The use of genetic material is considered one of the innovative methods for treating many hereditary and incurable diseases, as well as for conducting medical and scientific experiments to benefit from scientific advances in the medical field generally, and in genetics specifically. This topic has attracted the attention of religious scholars, legal experts, and medical professionals. Due to the absence of explicit texts prohibiting or permitting the sale of genetic material, specialists have resorted to ijtihad (independent reasoning) based on their perspectives on life and its philosophy, or based on what they perceive as the social interest in the process of selling genetic material.